Calibration of GafChromic EBT3 for absorbed dose measurements in 5 MeV proton beam and 60Co γ‐rays. Issue 8 (15th July 2015) - Vadrucci, M.; Esposito, G.; Ronsivalle, C.; Cherubini, R.; Marracino, F.; Montereali, R. M.; Picardi, L.; Piccinini, M.; Pimpinella, M.; Vincenti, M. A.; De Angelis, C.
Abstract : Purpose: To study EBT3 GafChromic film in low‐energy protons, and for comparison purposes, in a reference 60 Co beam in order to use it as a calibrated dosimetry system in the proton irradiation facility under construction within the framework of the Oncological Therapy with Protons (TOP)‐Intensity Modulated Proton Linear Accelerator for RadioTherapy (IMPLART) Project at ENEA‐Frascati, Italy. Methods: EBT3 film samples were irradiated at the Istituto Nazionale di Fisica Nucleare—Laboratori Nazionali di Legnaro, Italy, with a 5 MeV proton beam generated by a 7 MV Van de Graaff CN accelerator. The nominal dose rates used were 2.1 Gy/min and 40 Gy/min. The delivered dose was determined by measuring the particle fluence and the energy spectrum in air with silicon surface barrier detector monitors. A preliminary study of the EBT3 film beam quality dependence in low‐energy protons was conducted by passively degrading the beam energy. EBT3 films were also irradiated at ENEA‐National Institute of Ionizing Radiation Metrology with gamma radiation produced by a 60 Co source characterized by an absorbed dose to water rate of 0.26 Gy/min as measured by a calibrated Farmer type ionization chamber. EBT3 film calibration curves were determined by means of a set of 40 film pieces irradiated to various doses ranging from 0.5 Gy to 30 Gy absorbed dose to water. An EPSON Expression 11000XL color scanner in transmission mode was used for film analysis. Scanner response stability, intrafilm uniformity, and interfilm reproducibility were verified. Optical absorption spectra measurements were performed on unirradiated and irradiated EBT3 films to choose the most sensitive color channel to the dose range used. Results: EBT3 GafChromic films show an under response up to about 33% for low‐energy protons with respect to 60 Co gamma radiation, which is consistent with the linear energy transfer dependence already observed with higher energy protons, and a negligible dose‐rate dependence in the 2–40 Gy/min range. Short‐ and long‐term scanner stabilities were 0.5% and 1.5%, respectively; film uniformity and reproducibility were better than 0.5%. Conclusions: The main purpose of this study was to implement EBT3 dosimetry in the proton low‐energy radiobiology line of the TOP‐IMPLART accelerator, having a maximum energy of 7 MeV. Low‐energy proton and 60 Co calibrated sources were used to investigate the behavior of film response vs to be written in italicum dose. The calibration in 5 MeV protons is currently used for dose assessment in the radiobiological experiments at the TOP‐IMPLART accelerator carried out at that energy value.